Efeito agudo de uma sessão de treinamento físico com uso do Nintendo Wii® sobre aspectos psicológicos e cardiovasculares de adultos jovens, adultos e idosos - Alves, Raquel Cougo (2016)
Introduction: physical exercise has been the subject of numerous issues related to health due to evidence of its benefits to many individuals of different age groups. Obtain such benefits is of utmost importance in order to have a life with autonomy, well-being and healthy aging. Among the options exercise comes the virtual reality that enables the user interaction with the game through similar situations reality. The objective of this research was to analyze the effect of a session of physical exercises with the Nintendo Wii Fit® on the psychological and cardiovascular aspects of young adults, adults and seniors of both sexes. Methods: The subjects performed an exercise session through the Wii console, lasting 43 minutes, consisting of aerobic games, strength and balance. They evaluated the mood, affection, fun, perceived exertion, blood pressure, heart rate and double product of the participants. The Shapiro-Wilk test was used to verify the normality of the data; Descriptive statistics for the characterization of the variables; the paired t-test to check the difference between means and analysis of psychological variables; and Anova one way with post hoc Bonferroni for intra and inter-group comparison. The significance level was 5%. Results: during the exercise session individuals remained at a high level of activation, with a positive feeling and cardiovascular responses remained significantly above resting values. At the end of the session was obtained high degree of fun and improves the mood of the participants profile after completion of the session compared to the pre-session time. Conclusion: The physical training session with virtual reality promoted acute cardiovascular changes significantly higher than the rest period, generated positive effects on mood and affection of the participants and provided a high degree of fun to young people, adults and the elderly.